2022
DOI: 10.1039/d2tb01826h
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-methoxyethyl acrylate) coated bioprosthetic heart valves by copolymerization with enhanced anticoagulant, anti-inflammatory, and anti-calcification properties

Abstract: With the emergence of transcatheter aortic valve replacement (TAVR), commercial glutaraldehyde (Glut) cross-linked bioprosthetic heart valves (BHVs) fabricated from the xenogeneic pericardium have become the most popular choice for treating heart valve diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Liang et al 2022 [ 210] PP PMEA coating by copolymerization Enhanced anticoagulant, anti-inflammatory, and anti-calcification properties Wu et al 2018 [ 191] PP Extracellular matrix coating Immune response, potentially induce tissue regeneration, and improved biocompatibility Liu et al 2021 [ 211] PP Zwitterionic copolymer modification based on MPC Improved anti-coagulant and anti-calcification properties Marinval et al 2018 [ 212] PHV Fucoidan/VEGF-based surface modification…”
Section: Authors Years Bioprosthesis Materials Modification Strategie...mentioning
confidence: 99%
“…Liang et al 2022 [ 210] PP PMEA coating by copolymerization Enhanced anticoagulant, anti-inflammatory, and anti-calcification properties Wu et al 2018 [ 191] PP Extracellular matrix coating Immune response, potentially induce tissue regeneration, and improved biocompatibility Liu et al 2021 [ 211] PP Zwitterionic copolymer modification based on MPC Improved anti-coagulant and anti-calcification properties Marinval et al 2018 [ 212] PHV Fucoidan/VEGF-based surface modification…”
Section: Authors Years Bioprosthesis Materials Modification Strategie...mentioning
confidence: 99%
“…53,54 X-coating, or poly(2-methoxyethyl acrylate) (PMEA), has a hydrophobic polyethylene backbone on its lowest layer and a biologically inert hydrophilic layer on its surface; it is also an amphiphilic polymer with excellent hemocompatibility and can resist protein adsorption and platelet activation. 55 Marcoux et al showed that patients in the X-coating group spent significantly more time in the ICU for treatment and with ventilators, resulting in worse clinical outcomes than patients treated with Bioline, Trillium, and Phisio coatings. 28 The Balance Biosurface coating contains negatively charged sulfonated polymers that can contribute to anticoagulation and PEO which can ensure hydrophilicity.…”
Section: Biopassive Coatings For Commercial Usementioning
confidence: 99%
“…Such outcomes indicate that inhibiting the formation of thrombi not only enhances hemocompatibility but also bolsters the performance of medical devices. This is achieved by mitigating the risk of extreme immune reactions triggered by hyperactivation, which in turn supports more effective tissue regeneration (Hu et al, 2020;Liang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%